Enzymatic synthesis of lignin derivable pyridine based polyesters for the substitution of petroleum derived plastics - Alessandro Pellis (Nature Portfolio, 2019)
The increasing concern of global plastic pollution has led to an increase in the production and characterization of bio-based and biodegradable alternatives. Here the authors show the synthesis of a series of fully bio-based alternatives based on 2,4-, 2,5-, and 2,6- pyridinedicarboxylic acids, via enzymatic catalysis.